Les barrieres non tarifaires au commerce de la viande de boeuf: Incidences sur les exportations de l'Afrique tropicale - International Livestock Centre for Africa (1979)
Enumeration of non - tariff barriers facing meat exports and their impact on tropical African exports w. note on development efforts and prospects. Data on distribution of world beef imports and tropical African exports, beef prices in selected countries, and trend of beef exports from East Africa, Botswana and Swaziland.